Costs of treating diarrhoea in a children's hospital in Mexico City. - Phillips, M. (World Health Organization, 1989)
The treatment received by children aged under 5 years with diarrhoea was studied in the Hospital Infantil de México (Federico Goméz), Mexico City. The costs of treatment were calculated and estimates were made of how these had changed since the establishment of an oral rehydration unit in the hospital in 1985. The results indicate that drug treatment of outpatients was generally appropriate and inexpensive. In contrast, the cost of drugs for inpatients was considerably higher. The seriousness of the cases justified much of this additional expense for inpatients, but there is evidence that the costs could be reduced further without jeopardizing the quality of the care. Diagnostic tests were relatively expensive, frequently failed to identify diarrhoeal etiology, and their results correlated poorly with the treatment prescribed. The oral rehydration unit resulted in significant savings by causing a 25% fall in the number of inpatients with diarrhoea.